Testing the Operation of the Electromagnetic Current Meter in the Open Sea. Results of Comparing Measurements by the Electromagnetic Current Meter with Other Methods of Current Measurements and Calculations (Opyty Raboty s Elektromagnitnym Izmeritelem Techenii v Otkrytom More) - Moroshkin,K. V. (1963)
The current velocities and directions measured by the electromagnetic current meter (EMIT) are compared with the data obtained by the bifilar current recorder (STOK), the Alekseyev number printing recorder (BPV-2), the Makarov-Nansen (dynamic anomaly) method, and the so-called navigational ship drift method. The data are analyzed for the geographical location, depths at which the currents are measured, the stability of currents, the effect of wind, mobile and immobile water strata, the ocean depth, bottom profile, and coastal delineation. Thus, the degree of accuracy of the recordings by the EMIT apparatus in various hydrographical conditions is clarified. Special attention is paid to the effect of submarine trenches and elevations on the recordings of the instruments. Graphs and tables illustrate the current patterns at various depths, based on measurements by electromagnetic and other methods, made in the Kuril-Kamchatka region at various times in the preceding decade. (Author) Trans. of Akademiya Nauk SSSR. Institut Okeanologii. Trudy, v25 p78-87 1957, by M. Slessers. Also available as TT-63-24187.